Variação temporal e espacial da comunidade fitoplanctônica do alto rio Paraná e ambientes associados, na área de influência dos reservatórios de Porto Primavera e Rosana. - Scomparin, Vânia Mara Bovo (2011)
This study evaluated the seasonal variation of phytoplankton community, in composition, richness, density, biomass and functional groups (FG) of phytoplankton in the main channel of Upper Paraná River, in a floodplain lake, connected to this river, and in Baía River, downstream from Porto Primavera and Rosana Reservoirs. Monthly phytoplankton samplings were accomplished at subsurface, at seven sampling stations in the main channel of Paraná River, one at Baía River, and one at floodplain lake, during the period between May 2007 and April 2008. We identified 168 taxa, and Chlorophyceae was the most representative group. Low values of richness, density and biomass were registered in the main channel of Paraná River, and high biomass values, in Baía River and in floodplain lake. Cyanobacteria presented the greatest contribution to biomass in all sampling stations, except for floodplain lake, where Bacillariophyceae most contributed for this attribute. We verified 10 FGS (A, C, E, H1, J, K, M, P, W1 and X2) in the examined sampling stations. The low values of richness and the Cyanobacteria dominance in all sampling stations at Paraná River indicated instability in phytoplankton diversity of this river. The low biomass values in Paraná River were probably associated with the high flow of this river, and with the oligotrophication process due to retention and sedimentation of seston in the cascade of reservoirs located upstream, which have increased after the construction of the dam of Porto Primavera Reservoir. These processes were the main responsible for the low concentrations of phosphorus in Paraná River, and the reduced values of biomass of Bacillariophyceae, Chlorophyceae and Cryptophyceae. Rosana Reservoir presented greater influence as to the input of inoculums to Paraná River and to floodplain lake, when compared to the flow from Porto Primavera Reservoir. Their highest influence occurred during the high water period. Radiocystis fernandoi Kom. & Kom.-Legn., the main dominant species in the sampling station located immediately downstream from the mouth of Paranapanema River, presented effective dispersal in the others sampling stations in the Paraná River and in floodplain lake, with occurrence of colonization, however, only in floodplain lake. Baía River, which can be considered a storage zone of phytoplankton biomass, presented bloom of Dolichospermum planctonicum (Brun.) Wacklin, Hoffm. et Kom., exporting high values of biomass of this species to the downstream sampling station, in Paraná River, in the low water period. During the high water period, the Paraná River had strong lotic influence on Baía River, drastically reducing the phytoplankton biomass of the same, due to dilution effect. The low biomass values recorded in Paraná River with probable impact on trophic web indicate the need of continuous monitoring of phytoplankton in the main channel of this river. The influence of reservoirs upstream from Paraná River on the phytoplankton community of lentic environments connected to it, mainly due to exportation of Cyanobacteria inoculums, indicates the need of continuous monitoring on this community in the floodplain and in these reservoirs.